Stuff to know when you start school - Bull, Charlotte; Hilton, Helene (London Dorling Kindersley Limited, 2018)
A survival guide for the busiest job you'll ever have: being a toddler. Learn all the super-important life skills you need to become a big boy or girl with this ultimate guide to being a toddler and starting school. No matter what grown-ups tell you, being little is hard work. There's so much to learn from tying your shoelaces, finding the right hole for each arm in a jumper, remembering to say "please" and "thank you" (every single time!), understanding what this new baby is doing in YOUR house, sharing your toys with children you barely know, and a whole bunch of other things too
Linguistic notions
Keywords: Child development; Early Learning; First day of school; Preschool children